New perspectives on health professions students' e-learning: Looking through the lens of the "visitor and resident" model. (3rd July 2017) - Druce, Maralyn; Howden, Stella
Abstract: Background: The growth of e-learning in health professional education reflects expansion of personal use of online resources. Understanding the user perspective in a fast-changing digital world is essential to maintain the currency of our approach. Methods: Mixed methods were used to investigate a cohort of postgraduate, e-learning healthcare students' perspectives on their use of online resources for personal and/or professional roles, via questionnaire and student-constructed diagrams, capturing use of online resources (underpinned by White's model of "resident" and "visitor" online engagement). Semistructured interviews explored the use and value of resources afforded via the online environment. Results: The 45 study participants described a range of prior experiences with online resources in personal and professional capacities, but overall students tended to use online "tools" ("visitor" mode) rather than highly collaborative networks ("resident" mode). In relation to e-learning, the dominant interview theme was valuing knowledge transfer from the tutor and using "visitor" behaviors to maximize knowledge acquisition. Peer-learning opportunities were less valued and barriers to collaborative "resident" modes were identified. Conclusions: These findings help to inform e-learning course design to promote engagement. The results enable recommendations for use of the "Visitor and Residents" model and for planning activities that learners might utilize effectively.